The American Stop Smoking Intervention Study for cancer prevention: an overview. (1997) - Manley, M; Lynn, W; Payne Epps, R; Grande, D; Glynn, T; Shopland, D
Abstract : The American Stop Smoking Intervention Study (ASSIST) is a programme to implement proven interventions in 17 states across the United States. ASSIST applies all that we have learned in 10 years of research on tobacco use prevention and control. The goal of this seven-year project is to reduce the prevalence of smoking and cigarette consumption in the ASSIST states. The scientific basis for ASSIST is described, followed by a general description of the project and its current status in the 17 targeted states.